2011
DOI: 10.1002/btpr.712
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinert, an oxygen carrier, improves cell culture performance in deep square 96‐well plates by facilitating oxygen transfer

Abstract: In bioprocess development, the 96-well plate format has been widely used for high-throughput screening of production cell line or culture conditions. However, suspension cell cultures in conventional 96-well plates often fail to reach high cell density under normal agitation presumably due to constraints in oxygen transfer. Although more vigorous agitation can improve gas transfer in 96-well plate format, it often requires specialized instruments. In this report, we employed Fluorinert, a biologically inert pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…A geometry with baffled walls was developed by Funke et al They investigated different baffled geometries and found an optimal design in the shape of a 6‐petaled flower regarding the oxygen transfer rates. Another method for improving the mass transfer is the addition of an oxygen transfer enhancing substance like Fluorinert, as performed by Meyer et al…”
Section: Introductionmentioning
confidence: 99%
“…A geometry with baffled walls was developed by Funke et al They investigated different baffled geometries and found an optimal design in the shape of a 6‐petaled flower regarding the oxygen transfer rates. Another method for improving the mass transfer is the addition of an oxygen transfer enhancing substance like Fluorinert, as performed by Meyer et al…”
Section: Introductionmentioning
confidence: 99%
“…PFCs are created by complete fluorination of hydrocarbons (replacement of hydrogen with fluorine), which generates a biologically non-reactive moiety [19]. The presence of a dense electron cloud, higher ionization potential, and greater electron affinity give rise to the highly hydrophobic and fluorophilic structure of PFCs [20].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical oxygen carrier perfluorocarbons are organofluorine compounds and dissolve relatively high volumes of gases including oxygen, facilitating availability of oxygen, and being developed for blood substitutes (Cohn & Cushing, ). One of these compounds was tested in deep‐tube CHO cell cultures and found to improve culture performances because of improved oxygen supply (Meyer et al, ). To eliminate the confounding difference in physical dissociation and further investigate the role of hypoxia in promoting cell aggregation, eight (8) shake flasks of CHO cells were cultured at the low agitation speed (120 rpm) but half of them ( n = 4) were supported with a chemical oxygen carrier (Fluorinert FC‐770) at 20% v/v.…”
Section: Resultsmentioning
confidence: 99%